Productivity in professional tourist guides: a scale development study with mixed-methods sequential exploratory design - Sari, Dilara Bahtiyar; Yüzbaşioğlu, Nedim (Anais Brasileiros de Estudos Turísticos, 2024)
Tour guides have been described as being critical in the design and delivery of the tourism experience. It is obvious that the development of the field of tourist guidance, which is of the key players in the tourism sector and giving it the importance it deserves should be done in the light of academic studies in this field. The purpose of this study is specific to professional tourist guides productivity is to develop a perception scale. In the research, the exploratory sequential mixed method was adopted and acted with the idea of creating an original and native scale. Within the scope of this method, the qualitative stage was performed first and then the quantitative stage. The discovery of the perception of efficiency of professional tourist guides made the study original. It was written with the idea of filling such a gap in the literature and increasing the research to be conducted in the field of scale development for professional tourist guides.